2019
DOI: 10.1021/acs.biochem.8b01184
|View full text |Cite
|
Sign up to set email alerts
|

D1-S169A Substitution of Photosystem II Perturbs Water Oxidation

Abstract: In photosystem II (PSII), photosynthetic water oxidation occurs at the tetramanganese–calcium cluster that cycles through light-induced intermediates (S0–S4) to produce oxygen from two substrate waters. The surrounding hydrogen-bonded amino acid residues and waters form channels that facilitate proton transfer and substrate water delivery, thereby ensuring efficient water oxidation. The residue D1-S169 lies in the “narrow” channel and forms hydrogen bonds with the Mn4CaO5 cluster via waters W1 and Wx. To probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 73 publications
3
50
2
Order By: Relevance
“…The changes observed in the O4 channel were similar to the theoretical calculation that reported a proton release in the channel in the S 0 -to-S 1 transition (Saito et al, 2015). However, FTIR studies on the D1-S169A mutant, which perturbs the interaction of a water molecule hydrogen bonded to O4, showed only minor effects on the efficiencies or kinetics of the S i -state transitions (Shimada et al, 2020;Ghosh et al, 2019). In contrast, the S 2 state multiline EPR spectrum of the D1-S169A mutant differs significantly from that of wildtype (Ghosh et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The changes observed in the O4 channel were similar to the theoretical calculation that reported a proton release in the channel in the S 0 -to-S 1 transition (Saito et al, 2015). However, FTIR studies on the D1-S169A mutant, which perturbs the interaction of a water molecule hydrogen bonded to O4, showed only minor effects on the efficiencies or kinetics of the S i -state transitions (Shimada et al, 2020;Ghosh et al, 2019). In contrast, the S 2 state multiline EPR spectrum of the D1-S169A mutant differs significantly from that of wildtype (Ghosh et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…For identifying which amino acids outside the first coordination sphere of the Mn 4 CaO 5 are involved in the networks tuning the properties of the cluster, a great number of site‐directed mutants have been constructed and studied. Among the residues studied and belonging to either D1, or D2 or CP43 or CP47 there are: D1/E65, D2/E312 and D1/E329 (Service et al 2010), D1/R334, D1/Q165, D2/D307, D2/E308, D2/D310, D2/D323 (Service et al 2014) and D2/K317 (Pokhrel et al 2013, Suzuki et al 2013), D1/N181 (Pokhrel et al 2015), D1/N298 (Nagao et al 2017), D1/N87 (Banerjee et al 2018), D1/S169 (Ghosh et al 2019a), D1/P173 (Sugiura et al 2014b), CP43/R357 (Ghosh et al 2019b) and D1/V185 (Bao and Burnap 2015, Sugiura et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The changes observed in the O4-channel were similar to the theoretical calculation that reported a proton release in the channel in the S 0 -to-S 1 transition 21 . However, FTIR studies on D1-S169A mutant, which perturbs the interaction of a water molecule hydrogen-bonded with O4, showed only minor effects on the e ciencies or kinetics of the Si-state transitions 26,27 . In contrast, the S 2 -state multiline EPR spectrum of the D1-S169A mutant differs signi cantly from that of wild-type 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, FTIR studies on D1-S169A mutant, which perturbs the interaction of a water molecule hydrogen-bonded with O4, showed only minor effects on the e ciencies or kinetics of the Si-state transitions 26,27 . In contrast, the S 2 -state multiline EPR spectrum of the D1-S169A mutant differs signi cantly from that of wild-type 27 . A further theoretical study on the O4-channel showed that the removal of water molecules in the O4-channel results in a decrease in the S 2 /S 1 redox potential by ~80 mV 28 .…”
Section: Discussionmentioning
confidence: 99%